Initial tool wear behavior during machining of titanium metal matrix composite (TiMMCs). (November 2016) - Duong, XuanTruong; Mayer, J.R.R.; Balazinski, M.
Abstract: This article presents the findings from a study of the initial tool wear behavior when machining the TiMMCs. The results show that the initial wear mechanism of diffusion and adhesion are primarily found for all cutting conditions tested, even though it has been reported that abrasion is the most important mechanism when machining the metal matrix composites. Rapid wear occurs within a very brief period as soon as the cutting action begins and extends to only few seconds at the most. More importantly, we discovered in this study a new wear form, a hard thin layer, at the first transition period. In this case, the effect of chemical stresses under accelerated cutting force and cutting temperature gradient lead to the diffusion wear and built-up edge (BUE) where the tool layer material reacts spontaneously with atmospheric oxygen and oxidizes the titanium and aluminum. These elements then participate in the machining process where the combination of these diffusion wear layer are burnished thermo-chemically under high stress pressure and form a hard smooth layer at the first transition period. Therefore, this layer, herein coined "wear shield", is considered a protection layer at the beginning of the steady wear period. Highlights: The initial wear mechanism period differs completely from the wear mechanism at the steady wear period; rapidly wear occurs within a very brief period and extends to only ten seconds at the most. A new wear form discovered within this study, herein coined "wear shield", is considered as a protection layer for the steady wear period. Initial tool wear mechanism and initial cutting condition play a key role to the tool wear evolution over time and tool life during machining process.